1992
DOI: 10.1111/j.1365-2761.1992.tb00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Vibrio pathogens to cells of rainbow trout, Oncorhynchus mykiss (Walbaum)

Abstract: The attachment of Vibrio pathogens to cells of rainbow trout, Oncorhynchus mykiss (Walbaum), was studied by use of species-specific monoclonal antibodies and indirect FITCimmunofluorescence microscopy. Vibrio anguillarum, V. ordalii and V. parahaemolyticus attached to cultured cells of rainbow trout gonads, various tissues of cryostat sections of whole fish, and smears of gills, intestine, buccal mucosa and skin. The attachment was inhibited by prior incubation of bacteria with monoclonal antibodies at titres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…It is known that V. anguillarum serogroup O2 attaches to tissue, whereas V. anguillarum serogroup O1 attaches to mucus, which suggests that O2 strains may have an invasion strategy where it penetrates the mucous layer and epithelial cell surface without first being established on the mucosa (Knudsen et al, 1999). In addition, di#erent serogroups of V. anguillarum have been tested for attachment to di#erent tissues of rainbow trout, and V. anguillarum serogroup O1 and O2 showed the greatest attachment (Chen & Hanna, 1992). The attachment was inhibited by prior incubation of bacteria with specific antibodies (Chen & Hanna, 1992) and attachment of V. anguillarum to the gut of rainbow trout is greater in non-vaccinated fish than in vaccinated fish (Horne & Baxendale, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that V. anguillarum serogroup O2 attaches to tissue, whereas V. anguillarum serogroup O1 attaches to mucus, which suggests that O2 strains may have an invasion strategy where it penetrates the mucous layer and epithelial cell surface without first being established on the mucosa (Knudsen et al, 1999). In addition, di#erent serogroups of V. anguillarum have been tested for attachment to di#erent tissues of rainbow trout, and V. anguillarum serogroup O1 and O2 showed the greatest attachment (Chen & Hanna, 1992). The attachment was inhibited by prior incubation of bacteria with specific antibodies (Chen & Hanna, 1992) and attachment of V. anguillarum to the gut of rainbow trout is greater in non-vaccinated fish than in vaccinated fish (Horne & Baxendale, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, di#erent serogroups of V. anguillarum have been tested for attachment to di#erent tissues of rainbow trout, and V. anguillarum serogroup O1 and O2 showed the greatest attachment (Chen & Hanna, 1992). The attachment was inhibited by prior incubation of bacteria with specific antibodies (Chen & Hanna, 1992) and attachment of V. anguillarum to the gut of rainbow trout is greater in non-vaccinated fish than in vaccinated fish (Horne & Baxendale, 1983). The ability of V. anguillarum serogroup O2 to attach and penetrate epithelial cells may be important for the establishment of an infection and a specific antibody in the mucus might play an important role in preventing attachment and penetration of the epithelium of the fish gills, skin and fins.…”
Section: Discussionmentioning
confidence: 99%
“…For fish bacterial pathogens, Aeromonas hydrophila and some Vibrio strains were found to attach to collagen, fibronectin (Ascencio et al, 1990), fish mucus (Krovacek et al, 1987) and fish epithelial cells (Chen & Hanna, 1992 ;Miliotis et al, 1995 ;Tan et al, 1998). The presence of flagella (Merino et al, 1997) and LPS (Merino et al, 1996b) in A. hydrophila was suggested to mediate adherence.…”
Section: Abbreviationsmentioning
confidence: 99%
“…It was proposed that vibrios penetrated the mucosal surfaces (i.e. gastrointestinal tract), adhered to and invaded the fish epithelial cells, and then spread to other tissues and organs (Krovacek et al, 1987 ;Chen & Hanna, 1992 ;Olsson et al, 1996). Tissue culture cells, especially epithelial cells, have played a crucial role in investigating bacteria-host interactions because cultured cells are easy …”
Section: Adherence Of Vibrios In Various Conditionsmentioning
confidence: 99%
“…It has been observed that V. anguillarum is able to bind to a neutral glycosphingolipid (glucosylceramide) receptor on the epithelial cell surface of rainbow trout intestine (Irie et al 2004) which may explain some of the mechanisms of attachment observed in previous studies. In a previous study, Chen and Hanna (1992) recognized that V. anguillarum, V. ordalii and V. parahaemolyticus were able to attach to cultured rainbow trout cells of gonads, smears of gills, intestine, buccal mucosa and skin and cryostat sections of whole fish. Among the V. anguillarum strains, serotypes O1 and O2 showed the greatest attachment.…”
Section: Vibrio Anguillarummentioning
confidence: 99%